Breast cancer and hormone replacement therapy: collaborative reanalysis of data from 51 epidemiological studies of 52,705 women with breast cancer and 108,411 women without breast cancer - Beral, V; Bull, D; Doll, R; Key, T; Peto, R; Reeves, G; Calle, E; Heath, C; Coates, R; Liff, J; Franceschi, S; Talamini, R; et al. (1997)
Background. The Collaborative Group on Hormonal Factors in Breast Cancer has brought together and reanalysed about 90% of the worldwide epidemiological evidence on the relation between risk of breast cancer and use of hormone replacement therapy (HRT). Methods. Individual data on 52,705 women with breast cancer and 108,411 women without breast cancer from 51 studies in 21 countries were collected, checked, and analysed centrally. The main analyses are based on 53,865 postmenopausal women with a known age at menopause, of whom 17,830 (33%) had used HRT at some time. The median age at first use was 48 years, and 34% of ever-users had used HRT for 5 years or longer. Estimates of the relative risk of breast cancer associated with the use of HRT were obtained after stratification of all analyses by study, age at diagnosis, time since menopause, body-mass index, parity, and the age a woman was when her first child was born. Findings. Among current users of HRT or those who ceased use 1-4 years previously, the relative risk of having breast cancer diagnosed increased by a factor of 1.023 (95% CI 1.011-1.036; 2p = 0.0002) for each year of use; the relative risk was 1.35 (1.21-1.49; 2p = 0.00001) for women who had used HRT for 5 years or longer (average duration of use in this group 11 years). This increase is comparable with the effect on breast cancer of delaying menopause, since among never-users of HRT the relative risk of breast cancer increases by a factor of 1.028 (95% CI 1.021-1.034) for each year older at menopause. 5 or more years after cessation of HRT use, there was no significant excess of breast cancer overall or in relation to duration of use. These main findings did not vary between individual studies. Of the many factors examined that might affect the relation between breast cancer risk and use of HRT, only a woman's weight and body-mass index had a material effect: the increase in the relative risk of breast dancer associated with long durations of use in current and recent users was greater for women of lower than of higher weight or body-mass index. There was no marked variation in the results according to hormonal type or dose but little information was available about long durations of use of any specific preparation. Cancers diagnosed in women who had ever used HRT tended to be less advanced clinically than those diagnosed in never-users. In North America and Europe the cumulative incidence of breast cancer between the ages of 50 and 70 in never-users of HRT is about 45 per 1000 women. The cumulative excess numbers of breast cancers diagnosed between these ages per 1000 women who began use of HRT at age 50 and used it for 5, 10, and 15 years, respectively, are estimated to be 2 (95% CI 1-3), 6 (3-9), and 12 (5-20). Whether HRT affects mortality from breast cancer is not known. Interpretation. The risk of having breast cancer diagnosed is increased in women using HRT and increases with increasing duration of use. This effect is reduced after cessation of use of HRT and has largely, if not wholly, disappeared after about 5 years. These findings should be considered in the context of the benefits and other risks associated with the use of HRT.